Synergies between app-based car-related shared mobility services for the development of more profitable business models - Mireia Gilibert; Imma Ribas (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: Emerging shared mobility services are an opportunity for cities to reduce the number of car single trips to both improve traffic congestion and the environment. Users of shared mobility services, such as carsharing, ridesharing and singular and shared ride-hailing services, often need to be customers of more than one service to cover all their transport needs, since few mobility providers offer more than one of these services from a single platform. On the other hand, providers offering these services separately do not optimize costly resources and activities, such as the vehicles or the technology. Hence, the aim of this paper is to find synergies between the different app-based car-related shared mobility services that foster the development of new business models, to increase the profitability of these services. Design/methodology/approach: The research approach is built on the literature of car-related shared mobility services business models, supported by the review of certain outstanding services websites, and face-to-face interviews with users and drivers of these transport services. The analysis is presented by means of the Business Model Canvas methodology. Findings: Based on the synergies found, this paper suggests a few different approaches for services to share some resources and activities. Originality/value: This study identifies the common features of carsharing, ridesharing and singular and shared ride-hailing services to develop more profitable business models, based on providing the services in aggregated form, or outsourcing activities and resources. In addition, the implications of these proposals are discussed as advantages and drawbacks from a business perspective.
Keywords: 650; Shared transport services; car sharing; ride hailing; ride sharing; business model